2015
DOI: 10.17756/jrds.2015-007
|View full text |Cite
|
Sign up to set email alerts
|

NIDA-Drug Addiction Treatment Outcome Study (DATOS) Relapse as a Function of Spirituality/Religiosity

Abstract: BackgroundThe connection between religion/spirituality and deviance, like substance abuse, was first made by Durkheim who defined socially expected behaviors as norms. He explained that deviance is due in large part to their absence (called anomie), and concluded that spirituality lowers deviance by preserving norms and social bonds. Impairments in brain reward circuitry, as observed in Reward Deficiency Syndrome (RDS), may also result in deviance and as such we wondered if stronger belief in spirituality prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 32 publications
(28 reference statements)
0
19
0
5
Order By: Relevance
“…Despite treatment, 5-year relapse rates are as high as 70% for alcohol dependence, 78% for cocaine dependence and 97% for opioid dependence. 4 , 5 , 6 Moreover, for opioid dependence, pharmacological treatment mainly consists of harm reduction strategies, using opioid substitution with opioid agonists 7 , 8 and for cocaine dependence no effective pharmacological treatment is available at all. 9…”
Section: Introductionmentioning
confidence: 99%
“…Despite treatment, 5-year relapse rates are as high as 70% for alcohol dependence, 78% for cocaine dependence and 97% for opioid dependence. 4 , 5 , 6 Moreover, for opioid dependence, pharmacological treatment mainly consists of harm reduction strategies, using opioid substitution with opioid agonists 7 , 8 and for cocaine dependence no effective pharmacological treatment is available at all. 9…”
Section: Introductionmentioning
confidence: 99%
“…We consider the issue of spirituality here, as it provides the overarching context in which the construct of "God" is to be understood. The role of spirituality in 12 Step membership has been found to be associated with a positive outcome of SUD treatment (4,5,24), and as a mediator of the positive outcome associated with 12 Step recovery (25)(26)(27). Additionally, as noted above, the self-reported experience of "spiritual awakening," referred to in the last (12 th ) Step, has been found to be associated with both decreased craving among established 12 Step members (28) and leading to an increased likelihood of abstinent outcome following treatment (7,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…While our article covered heroin use, dependence, prevalence, abstinence, prevention, recovery, and relapse as physical and emotional problem; and more biological aspects were not reviewed, such as research by Blum, et al [97] who found that carriers of the DRD2 A1 allele bind together like "birds of a feather flock together" showing that there is even biological evidence for the importance of friendship networks. In addition, although we focused on employment issues, educational level [98] as well as religiosity [99] also have important implications for understanding this area. Also, many of the articles refer to psychoactive substances and are not specific to heroin.…”
Section: Recovery Homes As a Case Examplementioning
confidence: 99%